Fundamentals of Counseling Guidance in The Qur’an - Soleha, Sovatunisa; Kholila Harahap, Emmi; Saputra, Hasep (JIM - Journal International Multidisciplinary, 2023)
Islam said that labeling in counseling courses must refer to Islamic teachings which are rahmatan lil 'alamin and are closely related to the Al-Qur'an and Hadith as primary sources of law seeking. Therefore, the integration of the values ​​of the Koran and hadith is a necessity for both ontology, epistemology and axiology. Thus the Islamic counseling referred to in this description is different from conventional counseling originating from the West. Western Counseling talks about Self-Concept and Beliefs. More than just self-concept and self-confidence, Islamic counseling talks about the concept of the Qur'an and Hadith which emphasizes monotheism as a servant in the right position and position of proportion. By using a literature study method that refers directly to the Al-Qur'an, the following series of paragraphs will focus more on elaborating on the basics of the Qur'an in counseling.